lim(x- -3) (x^2 - 9)/(root[x^2 + 16]-5)

limx-3 x2 - 9x2 + 16 - 5 = limx-3 x2 - 9x2 + 16 - 5 ×x2 + 16 + 5x2 + 16 + 5      = limx-3 x2 - 9 x2 + 16 + 5x2 + 162 - (5)2 =  limx-3 x2 - 9 x2 + 16 + 5x2 + 16 - 25=limx-3 x2 - 9 x2 + 16 + 5x2 - 9 =limx-3  x2 + 16 + 5 = (-3)2 + 16 + 5 = 25 + 5 = 5 + 5 = 10

  • 2

that's limit(x tends to -3)

  • -1

wow nice question buddy.... hold a sec ill try

  • 1

Ok its an easy one... heres ur answer....

.

= limit (x tending to -3) of { [x^2 - 9] / [root(x^2 + 16) - 5] }

.

Multiplying and dividing by[root(x^2 + 16) + 5] to rationalise the denominator:-

.

=limit (x tending to -3) of {[x^2 - 9] *[root(x^2 + 16) + 5]/ [root(x^2 + 16) - 5] *[root(x^2 + 16) + 5]}

=limit (x tending to -3) of { [x^2 - 9] *[root(x^2 + 16) + 5]/ [x^2 + 16 - 52] }

=limit (x tending to -3) of { [x^2 - 9] *[root(x^2 + 16) + 5]/ [x^2 + 16 - 25] }

= limit(x tending to -3) of { [x^2 - 9] *[root(x^2 + 16) + 5]/ [x^2 - 9] }

.

Here we can cancel out[x^2 - 9] in denominator and numerator.

.

=limit(x tending to -3) of { [x^2 - 9] *[root(x^2 + 16) + 5]/ [x^2 - 9] }

= limit(x tending to -3) of [root(x^2 + 16) + 5]

= [root(9+16) + 5]

= root(25) + 5

= 5 + 5

= 10

.

  • 0

thanks..!!

  • 2
What are you looking for?